Livre expressão :para que te quero? o interesse público no ensino do Jornalismo - Souza, Cristóvão Pereira (2006)
The main objective of this research was studying the meanings of the freedom of expression and what professors of Journalism think about the way those meanings are used in pedagogical practices. The term freedom of expression is commonly used in journalism even though it is not so studied, consequently we don t have a word to define it. Therefore, we related the term freedom of expression in Journalism teaching to the condition as the object of this study, aiming to establish a connection among the term, the right, free expression and the endurance of the right. The theorical support to understand the dynamic of the meanings of the freedom of expression in the social practice of Journalism teaching was based in the Hegeliana dialetic theorical principles and in the language philosophy more specifically in Bakhtin s perspective from which we can mention the social auditorium, immediate conditions of production and a wider social horizon as the main categories of analysis. This study is a qualitative research with an interacionist perspective anchored in a semi-structured interview as a privileged method of data collecting made with ten professors from Journalism graduation. The analysis reveals that, in the interviewers perspective, there would be a deceiving practice from freedom of expression in the journalism teaching in which emerges either in speeches with handbills spreading the fear and/or under a stimulus form to concealment